(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: The first objective is to assess the discontinuation rate of antihypertensive medications on the day of scheduled surgery. The second objective is to compare medication continuation rates before and after implementing a coordinated management protocol. Materials and methods: Adult hypertensive patients scheduled for surgery were divided into two groups. An observational study evaluated the first objective, while an interventional study addressed the second. Results: The observational study included 121 patients and reported that 39.7% continued their antihypertensive medications on the day of scheduled surgery. In the control group, which included 34 patients before the implementation of the protocol, 67.6% continued their medication. In the intervention group, which comprised 30 patients post-implementation, the continuation rate was 86.7% (p=0.073). Conclusions: The discontinuation of antihypertensive medications on the day of scheduled surgery remains prevalent. Implementing a multidisciplinary management protocol for antihypertensive medications could potentially improve the continuation rates of these medications on the day of scheduled surgeries.